Urban–rural differences in the prevalence of diabetes mellitus among 25–74 year-old adults of the Yangon Region, Myanmar: two cross-sectional studies - Espen Bjertness; Hein Stigum; Wai Phyo Aung; Aung Soe Htet; Virasakdi Chongsuvivatwong; Marte Karoline Råberg Kjøllesdal (BMJ Open)
Objectives To investigate the association between urban–rural location and the occurrence of diabetes mellitus (DM) in the Yangon Region, and to estimate the proportion of urban and rural participants already diagnosed with DM, and of those, the proportion under treatment and under control.Design Two cross-sectional studies, using the WHO STEPs methodology.Setting The Yangon Region of Myanmar, urban and rural areas.Participants Men and women, aged 25–74 years, included during the study period from September–November 2013 (urban) and 2014 (rural areas) (n=1372). Institutionalised people, physically and mentally ill person, monks and nuns were excluded.Results The age-standardised prevalence of DM was 12.1% in urban and 7.1% in rural areas (p=0.039). In urban areas, the prevalence of DM was lowest in the highest educational groups (p<0.001). There were no differences in DM prevalence between gender or income levels. In rural areas, those who were physically inactive had a low intake of fruit and vegetable and were overweight/obese had a higher DM prevalence than others. In a logistic regression, the OR for DM in rural compared with urban areas was 0.38 (0.22, 0.65), adjusted for sociodemographic variables and behavioural risk factors. In urban areas, 43.1% of participants had the experience of receiving blood glucose measurements by a doctor or health worker, and 61.5% of all cases of DM were already diagnosed, 78.7% were under treatment and 45.8% were under control. The corresponding proportions in rural areas were 26.4%, 52.4%, 78.1% and 32.0%, respectively.Conclusion The prevalence of DM in the Yangon Region was high, and significantly higher in urban than in rural areas. More health services are needed to serve this population with a large proportion of undiagnosed diabetes. Preventive measures to halt and reduce the prevalence of DM are urgently needed.